Effects of self-regulation prompts in hypermedia learning on learning performance and self-efficacy. (December 2018) - Müller, Nadja M.; Seufert, Tina
Abstract: Learning with prompts activates self-regulation processes often resulting in increased learning performance. As experiences of self-regulation and learning success are sources of self-efficacy, the study investigated whether prompts affect learning performance over two learning sessions and examines whether prompts affect learners' self-efficacy perceptions within and across these sessions. N = 52 students learned twice for 30 min in a hypermedia either receiving prompts or learning without. In each session, self-efficacy was assessed before, during, and after learning while performance was measured at the end. Prompted learners outperformed learners without prompts only in the first performance test regarding transfer. Additionally, they reported higher overall self-efficacy. While self-efficacy perceptions did not differ between groups in the first learning session, self-efficacy perceptions in the second learning session were higher amongst prompted learners. Results indicate that learning with prompts may foster self-efficacy across learning sessions. Navigation behavior did not differ between groups. Underlying mechanisms and longer-term effects of prompts need to be further researched. Highlights: Self-regulation is important for effective hypermedia learning. Self-regulation prompts were used to foster learning performance and self-efficacy. The study considers prompts within the dynamic nature of self-regulation processes. Prompts only fostered transfer performance in the first learning session. Prompting increased self-efficacy across but not within two learning sessions.